2017
DOI: 10.1371/journal.pone.0185694
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and maintenance of corneal thickness during aging

Abstract: Corneal thickness is tightly regulated by its boundary endothelial and epithelial layers. The regulated set-point of corneal thickness likely shows inter-individual variations, changes by age, and response to stress. Using anterior segment-optical coherence tomography, we measure murine central corneal thickness and report on body size scaling of murine central corneal thickness during aging. For aged-matched mice, we find that corneal thickness depends on sex and strain. To shed mechanistic insights into thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
(30 reference statements)
2
8
0
Order By: Relevance
“…While the anterior corneal epithelium thickened from 8 to 20 weeks in both strains, it was thinner in BXSB-Yaa than in BXSB at 28 weeks. Consistent with our results, the anterior corneal epithelium thickens with ageing in healthy mice, 33 and dry eye model mice have thinner corneal epithelium due to cell injuries than healthy controls. 10 A previous study showed that tear film instability could cause potential damage to the ocular surface.…”
Section: Discussionsupporting
confidence: 91%
“…While the anterior corneal epithelium thickened from 8 to 20 weeks in both strains, it was thinner in BXSB-Yaa than in BXSB at 28 weeks. Consistent with our results, the anterior corneal epithelium thickens with ageing in healthy mice, 33 and dry eye model mice have thinner corneal epithelium due to cell injuries than healthy controls. 10 A previous study showed that tear film instability could cause potential damage to the ocular surface.…”
Section: Discussionsupporting
confidence: 91%
“…Especially in the case of DED, non-contact measurement methods are preferred because the patients with DED are more susceptible to corneal epithelial damage and infection [26]. Recently, several units of non-contact tonometry and pachymetry have been developed for clinical and small-animal imaging [27]. Pentacam (OCULUS, Optikgerate GmbH, Wetzlar, Germany), a rotating Scheimpflug camera, and anterior segment optical coherence tomography (ASOCT) determine the CCT, TCT, and the thinnest point of the cornea.…”
Section: Introductionmentioning
confidence: 99%
“…11,61,62 Thus, although endothelial cell density was not quantified in the current study, it is likely that the observed increase in stromal thickness could be explained by an age-related decline in endothelial cell density. Inomata et al 19 also reported an increase in the corneal thickness, but no change to epithelial thickness, of BALB/c mice at 14 months of age. This disparity may be accounted for by the genetic variation between different mouse strains and different ages.…”
Section: Discussionmentioning
confidence: 92%
“…However, there remains inconsistency with respect to the reported impact of aging on other ocular surface parameters, such as corneal thickness, where some studies have reported no age-related changes, 17,18 and others have shown an increased thickness compared with young mice. 19 In addition, the effects of aging on corneal immune responses, in particular the number, distribution, and morphology of resident epithelial dendritic cells (DCs), is unclear. The normal corneal epithelium has a resident population of DCs that have been well characterized in both humans and rodents.…”
mentioning
confidence: 99%